Inducible developmental reprogramming redefines commitment to sexual development in the malaria parasite Plasmodium berghei. (November 2018) - Kent, Robyn; Modrzynska, Katarzyna; Cameron, Rachael; Philip, Nisha; Billker, Oliver; Waters, Andrew
Abstract During malaria infection, Plasmodium spp. parasites cyclically invade red blood cells and can follow two different developmental pathways. They can either replicate asexually to sustain the infection, or differentiate into gametocytes, the sexual stage that can be taken up by mosquitoes, ultimately leading to disease transmission. Despite its importance for malaria control, the process of gametocytogenesis remains poorly understood, partially due to the difficulty of generating high numbers of sexually committed parasites in laboratory conditions1 . Recently, an apicomplexa-specific transcription factor (AP2-G) was identified as necessary for gametocyte production in multiplePlasmodium species2, 3, and suggested to be an epigenetically regulated master switch that initiates gametocytogenesis4, 5 . Here we show that in a rodent malaria parasite, Plasmodium berghei, conditional overexpression of AP2-G can be used to synchronously convert the great majority of the population into fertile gametocytes. This discovery allowed us to redefine the time frame of sexual commitment, identify a number of putative AP2-G targets and chart the sequence of transcriptional changes through gametocyte development, including the observation that gender-specific transcription occurred within 6 h of induction. These data provide entry points for further detailed characterization of the key process required for malaria transmission. The conditional overexpression of the transcription factor AP2-G inPlasmodium berghei enables the large-scale conversion of parasite populations into gametocytes, facilitating analysis of the sexual commitment stage of the parasite life cycle.